2002
DOI: 10.1034/j.1600-6143.2002.20611.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity Greatly Influences Cytokine Gene Polymorphism Distribution

Abstract: Polymorphisms in the regulatory regions of cytokine genes are associated with high and low cytokine production and may modulate the magnitude of alloimmune responses following transplantation. Ethnicity influences allograft half-life and the incidence of acute and chronic rejection. We have questioned whether ethnic-based differences in renal allograft survival could be due in part to inheritance of cytokine polymorphisms. To address that question, we studied the inheritance patterns for polymorphisms in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
208
10
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(240 citation statements)
references
References 38 publications
18
208
10
4
Order By: Relevance
“…20,[28][29][30][31] The frequency of the À308 A allele is lower in those of African descent (10%). 31,32 Possible explanations for this observation are that the À308 A allele increases risk for preterm delivery, or increases need for MV at birth, or both. Indeed, preliminary reports suggest a role for this polymorphism in the etiology of preterm births.…”
Section: Discussionmentioning
confidence: 99%
“…20,[28][29][30][31] The frequency of the À308 A allele is lower in those of African descent (10%). 31,32 Possible explanations for this observation are that the À308 A allele increases risk for preterm delivery, or increases need for MV at birth, or both. Indeed, preliminary reports suggest a role for this polymorphism in the etiology of preterm births.…”
Section: Discussionmentioning
confidence: 99%
“…51 Pravica et al 52 and others have shown that the I1(761)*CA 12 allele is associated with increased expression of IFNg mainly in homozygotes, although a trend toward increased expression was observed in heterozygotes, findings confirmed by others. [53][54][55] Pravica et al 56 also reported that an SNP in intron 1 [I1(759)*T-A] is in tight LD with I1(761)*CA n . The high-secretory I1(761)*CA 12 allele is in strong LD with I1(759)*T. Homozygosity for the I1(759)*A allele is associated with a 3.8-fold increase in risk of tuberculosis in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that there are significant differences in IL-2 genotype frequencies observed in different populations. Recent studies have shown that inheritance of polymorphic cytokine gene alleles is dramatically influenced by ethnicity (Cox et al, 2001;Hoffmann et al, 2002). Moreover, a statistically significant ethnicity-based variability in the allelic frequency and genotype inheritance patterns for IL-2 and IL-6 has been reported (Cox et al, 2001), suggesting that polymorphisms within these cytokine genes may be responsible for the ethnic-based differences in IL-2 or IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%